STUDI KOORDINASI KERJA RELAI JARAK SEBAGAI PENGAMAN CADANGAN PADA SALURAN 150 KV GIS PESANGGARAN-GI NUSA DUA - Deoka Gusti; I Gede Dyana Arjana; Cokorde Gede Indra Partha (Jurnal SPEKTRUM, 2021)
The development of Pesanggaran Conventional Substation into the Pesanggaran GasInsulated Switchgear (GIS) as a form of increasing the reliability of the electric power system inBali which led to changes in the protection system configuration on the transmission lineconnecting the GIS Pesanggaran and Nusa Dua Substation. The distance relay that waspreviously functioning as a primary protection was changed to backup protection due to the lackof selectivity of the distance relay in isolate the disruption and as the backup protection if themain protection experiencing a failure. Simulation testing using power system analysis softwareafter determining the value of the distance relay setting and tested with short circuit at 110%and 180% of the transmission line length shows the distance relay has worked according to theP3B JB regulation No. 211/151/P3B/2010 and distance relay can detect disruption in zone 2with a delay time of 0,815 seconds and detect disruption in zone 3 with a delay time of 1,615seconds.